2014
DOI: 10.1002/ptr.5164
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti‐atopic Dermatitis Activity of Hypsizigus marmoreus Extract

Abstract: Hypsizigus marmoreus is an edible mushroom that is cultivated worldwide. In this study, we investigated antiinflammatory activities of H. marmoreus extract on atopic dermatitis (AD)-like symptoms. Ethanol extract of H. marmoreus (HMEE) was administrated in powder to BALB/c mice in which AD was induced by 1-chloro 2, 4, 6-trinitrobenzene [picryl-chloride, (PCL)]. The dermatitis severity score and the thickness of the epidermis were significantly decreased following daily intake of HMEE powder (1 g/kg/day) for 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
1
4
1
Order By: Relevance
“…We found that in AD skin lesions, the IL-1β level was significantly decreased and infiltration of mast cells was reduced after 4 weeks of HW administration, indicating amelioration of the proinflammatory environment. Consistent with our results, previous studies showed that some natural extracts mitigated AD by reducing IL-1β expression and infiltration of mast cells into the dermal and subcutaneous layers of AD mice, 15 , 16 confirming that IL-1β and mast cells are associated with AD severity. We also found that the level of IL-33, which is known to be expressed by activated mast cells 13 was lower in the HW group.…”
Section: Discussionsupporting
confidence: 92%
“…We found that in AD skin lesions, the IL-1β level was significantly decreased and infiltration of mast cells was reduced after 4 weeks of HW administration, indicating amelioration of the proinflammatory environment. Consistent with our results, previous studies showed that some natural extracts mitigated AD by reducing IL-1β expression and infiltration of mast cells into the dermal and subcutaneous layers of AD mice, 15 , 16 confirming that IL-1β and mast cells are associated with AD severity. We also found that the level of IL-33, which is known to be expressed by activated mast cells 13 was lower in the HW group.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, treatment of BALB/c mice with ethanol extracts of HM was shown to lower the TNF␣ or interleukin 6 expression, much as in our present study, but there were no changes in body weight (12). Furthermore, the components of the ethanol extract of HM were also not identifi ed in this study.…”
Section: Discussioncontrasting
confidence: 52%
“…Only 5 mg of EHM obtained with ethanol was used on each mouse to investigate the effects on pro-infl ammatory cytokines (12). Considering the results of the ethanol extraction experiment, we instead used 10 mg and 1 mg of EHM/20 g of body weight per mouse for once-daily treatment to determine the effects of EHM on centage of total body components was analyzed by the DXA method in the EHM group (white column; EHM) and the control group (black column; Cont) (A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the soluble fraction of the n -butanol extract proved to have the most hair growth promoting activity among those extracts in vivo ( Figure 3 ). Recently, many research groups have suggested that traditional foods, plants, and grains, and so forth, have new pharmaceutical potential, but those investigators have mostly used soluble fractions extracted with one solvent and they discarded the insoluble fractions of the extract [ 7 , 17 ]. That approach seems to be sufficient enough to show whether or not pharmaceutical activity exists in those materials; however, many additional steps should be considered in developing therapeutics using those materials.…”
Section: Discussionmentioning
confidence: 99%